Analysis of Service Management on the Quality of Public Services: Case Study of One of the Midwives' Practices in Soreang, Bandung Regency - Fikry Firmansyah (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
A midwife is a woman who has successfully finished a government-recognized Midwifery education program, either nationally or internationally and has fulfilled the necessary criteria to practice Midwifery. The significance of public service quality and midwives underscores the crucial contribution of midwives in delivering high-quality health care to the community. This study seeks to enhance the service management employed by a midwifery practice in Soreang, Bandung Regency, concerning the quality of public services. This research employs a descriptive qualitative approach utilizing observation and interview techniques, comprising 15 participants, including midwives, administrative personnel, and patients. The study's findings demonstrate that the service quality at a Midwife Practice in Soreang, Bandung Regency, aligns with the standards of Reliability, Responsiveness, Tangibility, Assurance, and Empathy. The current service system adheres to the principles of simplicity and transparency, resulting in health care quality management at a Midwife Practice in Soreang, Bandung Regency, being widely regarded as satisfactory.